PENGARUH ETOS KERJA, INSENTIF DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN HOTEL MALAKA BANDUNG - Rahadiyan Rahadiyan; Ida Bagus Alit Ksama Putra; Ceria Febiana; Tata Dibrata; Risna Haryati; Putri Dwi Novrina; I Putu Ajie Windu Kertayoga (Universitas Nurtanio Bandung, 2023)
This study aims to examine the effect of: (1) work ethic, incentive and career development on employee performance, (2) work ethic on employee performance, (3) incentive on employee performance, (4) career development on employee performance. Research design used in this study is causal quantitative research. In this study, the subjects were employees at Malaka Bandung Hotel and the objects of research were work ethic, incentive, career development and employee performance. Total population for this study was all employees at Hotel Malaka Bandung totaling 35 employees. Data was collected by interviews, document recording and questionnaire methods, and then analyzed by multiple regression analysis. The results showed that: (1) work ethic, incentive and career development have a significant effect on employee performance, (2) work ethic has a significant effect on employee performance, (3) incentive has a significant effect on employee performance, (4) career development has a significant effect on employee performance.